2022
DOI: 10.3390/buildings12122077
|View full text |Cite
|
Sign up to set email alerts
|

Surveys on Noise in Some Hospital Wards and Self-Reported Reactions from Staff: A Case Study

Abstract: Noise in hospital wards adversely affects the physiological processes of both patients and staff and it is a potential risk for communication breakdowns and errors, causing discomfort and problems regarding the healing of patients, as well as stress, fatigue, and annoyance for staff. Several noise sources are present in the wards, such as HVAC systems, alarms, paging, speech, calls, diagnostic equipment, medical devices, and so forth. This paper describes two surveys carried out at an Italian hospital in Rome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As suggested by reports from the World Health Organization (WHO) [1,8] and the European Environment Agency (EEA) [1,9], noise exposure is a major public health threat affecting both physical and mental health. Many studies have focused on the relationship between noise exposure and people's health [10][11][12][13]. A common health problem is noiseinduced hearing loss.…”
Section: Noise Exposure and Human Healthmentioning
confidence: 99%
“…As suggested by reports from the World Health Organization (WHO) [1,8] and the European Environment Agency (EEA) [1,9], noise exposure is a major public health threat affecting both physical and mental health. Many studies have focused on the relationship between noise exposure and people's health [10][11][12][13]. A common health problem is noiseinduced hearing loss.…”
Section: Noise Exposure and Human Healthmentioning
confidence: 99%
“…In the literature, a clear correlation emerges between noise level, number and frequency of noise events, and disturbance on users (both in patients, during night hours, and in medical personnel, during working hours). For this reason, many studies place the subjective user response alongside the objective measurement data, by analyzing psychoacoustic parameters [10], generally used in soundscape analyses [11,12] combined with quantitative surveys, based on questionnaires or qualitative surveys, using post-hospitalization interviews, [13][14][15][16][17][18]. Since studies are conducted in various ways, there is a need for a more comprehensive standardization strategy to balance noise measurement procedures in indoor hospital environments [9].…”
Section: Acoustics In Hospital Environmentmentioning
confidence: 99%
“…The study by Lam et al [19] revealed that personnel perceived the overall acoustic quality of hospitals as less suitable than patients and visitors did. Lo Castro et al [22] demonstrated that the acoustic environment in several hospitals was reported as largely noisy by the personnel and was correlated with the concentration loss.…”
Section: Introductionmentioning
confidence: 99%